Management Potential Development and Analysis of Cost Return of Organically-Dyed Weaving of the Weaving Community Enterprise Groups in Borabue District, Maha Sarakham Province - Aeksapang, Jaruwan; Ongklang, Ailadda; Wongmangkorn, Sarada; Phongsart, Piyaphon (Chophayom Journal, 2024)
Research on the subject “Human resource management potential development and analysis of cost return of organically-dyed weaving of the weaving community enterprise groups in Borabue district, Maha Sarakham province aimed to 1) study on the community context of the weaving community enterprise groups; and 2) study on the costs and returns from natural color dyed fabric weaving of the Weaving community enterprise groups in Borabue district, Maha Sarakham province. The population in this study was the Weaving community enterprise groups in Maha Sarakham province. There were different areas from two sub-district, and two community enterprise groups in each district. Researcher had collected data from the interview with the Weaving community enterprise groups and used the interviewing form. Filled data in the interviewing forms were analyzed to explain the general characteristics of samples to answer the research questions using the Return on Invested Capital calculation. Research results from the membership data in Weaving community enterprise groups in Borabue district, Maha Sarakham province showed that most of them were female aged over than 45 years old onward and 41-45 years old. The number of family members were around 4-6 persons. From the data related to the Weaving community enterprise groups in Borabue district, Maha Sarakham province, most of them used synthetic colors and some natural colors. Weaving was an additional occupation. They did not form up as a group or cooperative. The weaving experience of members was more than 16 years. The areas used for weaving were belong to their own. Times for weaving were throughout the year. The key materials used in weaving were for example, Kaen Fang, blood soap, turmeric and Paduak. The source of key materials came from nature, none purchasing, and asking from other members. They used their own capital and supporting funds. They obtained knowledge from the village’s representatives, or government officers. Problems and obstacles for the weavers were the lack of capital and inhospitable area. The management control of the Natural Dyed Fabric Community Enterprise Group expressed opinions regarding the overall control of the organization very clearly. Weaving community enterprise groups in Borabue district, Maha Sarakham province generated incomes from weaving in four groups of weaving community enterprise in four months period. They could sell 187 of weaving clothes in which accounted to be the amount of 505,700 baht. The total production costs of the groups was at 231,000 baht. The highest cost was the cost of cotton dyeing and production cost. In summary, profit and loss from the operation of Weaving community enterprise groups in Borabue district, Maha Sarakham province were at the amount of 234,550 baht. From the analysis on the returns of investment, it was found at the rate of 86.64 percent. Keywords: Management Potential Development, Analysis of Cost Return, Organically-Dyed Weaving